Multivariate base rates of score elevations on the BRIEF2 in children with ADHD, autism spectrum disorder, or specific learning disorder with impairment in reading. Issue 7 (3rd October 2022) - Aita, Stephen L.; Holding, Emily Z.; Greene, Jennifer; Carrillo, Alicia; Moncrief, Grant G.; Isquith, Peter K.; Gioia, Gerard A.; Roth, Robert M.
ABSTRACT: There is a paucity of research examining multivariate base rates (MBRs) of elevated scores in pediatric rating scales of cognition. We present novel MBR information on the Behavior Rating Inventory of Executive Function, Second Edition (BRIEF2) for several clinical groups: Attention-Deficit/Hyperactivity Disorder Combined Presentation (ADHD-C); ADHD Inattentive Presentation (ADHD-I); Autism Spectrum Disorder (ASD); and Specific Learning Disorder with impairment in Reading (SLD-R). Participants included children diagnosed as having ADHD-C ( n  = 350), ADHD-I ( n  = 343), ASD ( n  = 390), or SLD-R ( n  = 240). Cumulative MBRs (e.g., the % of a sample having one or more elevated scores) were examined for each BRIEF2 form (Parent, Teacher, and Self-Report) and at three T -score cutoffs ( T  ≥ 60, T  ≥ 65, and T  ≥ 70). The MBR of obtaining at least one elevated score was common across clinical groups and forms at T  ≥ 60 (ADHD-C = 90.5–98.1%; ADHD-I = 83.9–98.7%; ASD = 90.3–96.9%, SLD-R = 60.0–78.4%), T  ≥ 65 (ADHD-C = 66.7–97.2%; ADHD-I = 77.5–94.9%; ASD = 77.3–92.7%; SLD-R = 38.5–64.0%), and T  ≥ 70 (ADHD-C = 52.4–89.4%; ADHD-I = 64.8–84.2%; ASD = 54.5–83.2%; SLD-R = 26.9–44.1%). MBRs appeared to differ as a function of group (ADHD-C > ADHD-I > ASD > SLD-R) and form (Parent > Teacher > Self-Report) though future research with well-defined samples is needed to investigate this. We provide novel MBR information to enhance clinical interpretation of BRIEF2 data.